Surface water and sediment geochemistry in understanding mobility of nitrates in mesic Kansas grassland - Eke, O.C. Enyinna (Kansas State University, 2011)
To understand ambient nitrate dynamics in an unmanaged grassland environment, the stable isotope chemistry of various substrates at the Konza Prairie Biological Station were studied. Sediments consisted of alluvium, loess and bedrock materials are mostly limestone and shale. To gain a better understanding of the biogeochemistry of N cycling in this unmanaged grassland, 34 water samples have been collected along a full stretch of the major onsite creeks (Kings and Shane Creeks). These samples have been analyzed for δD, δ18O, and δ15N to determine the manner by which water allows nitrates to be leached into sediment, and to determine if additional nitrate is contributed from weathering of the bedrock. The anion chemistry of the waters show the presence of bicarbonates, sulfates, chlorides, nitrates, and fluorides. Although an obvious correlation among the anions is not present, data shows high alkalinity content due to the presence of shallow bedrock that is continuously being weathered. Using a hydraulic geoprobe, sediment cores were collected up to 8 ft deep using 2 ft core liners adjacent to the creeks to study δ15N and δ13C spatial variation of the sediments. This research also indicated the presence of C3 and C4 derived soil organic carbon with the latter being dominant. There is also an approximate 1:9 correlation between the total nitrogen and carbon content of these core sediments including NO3 and NH4 that are mostly concentrated in the upper 2 – 4 ft of the sediment profile. The results of this study provide a broader context for ambient nitrate cycling in unmanaged grassland and a baseline comparison for nitrate levels in surrounding agricultural lands.
Keywords: nitrates; isotopes; Environmental Geology (0407)